Asymmetric Organocatalytic Cyclopropanation on Chiral Menthyl Acrylate for the Synthesis of (–)-trans-2-Aminomethylcyclopropanecarboxylic Acid [(–)-TAMP] - Sugeno, Yuka; Ishikawa, Yuichi; Oikawa, Masato (Synlett, 2014)
An enantioselective synthesis of (–)-trans-2-aminomethylcyclopropanecarboxylic acid [(–)-TAMP], a partial agonist for GABAc receptor, has been achieved as the hydrochloride salt in 3.9% overall yield for total eight steps from l-menthol. The synthesis features double asymmetric cyclopropanation that employs cinchona alkaloid derived organocatalyst and l-menthyl chiral auxiliary.
Keywords: amino acids; asymmetric catalysis; carbocycles; chiral auxiliaries; diastereoselectivity